2019
DOI: 10.1001/jamanetworkopen.2019.4330
|View full text |Cite
|
Sign up to set email alerts
|

Association of Frailty and Postoperative Complications With Unplanned Readmissions After Elective Outpatient Surgery

Abstract: Key Points Question Is frailty, as measured by the Risk Analysis Index, associated with risk for unplanned readmission after elective outpatient surgery? Findings In this cohort study of 417 840 patients in the National Surgical Quality Improvement Program, frailty was associated with an increased risk for unplanned readmissions after elective outpatient surgery. Mediation analysis showed that the association of frailty with readmission was partially mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 56 publications
2
52
0
2
Order By: Relevance
“… 4 It has become a well-established predictor of poor postoperative outcomes including an increased risk for complications and a longer length of stay in many of the surgical sub-specialties. 5 , 6 , 7 Recently, Berian et al demonstrated that the increase in complications seen in our older patient population was significantly associated with an increased rate of loss of independence and early mortality. 8 Frail surgical patients who suffer loss of independence often are placed in skilled nursing facilities upon discharge from the hospital.…”
Section: Introductionmentioning
confidence: 82%
“… 4 It has become a well-established predictor of poor postoperative outcomes including an increased risk for complications and a longer length of stay in many of the surgical sub-specialties. 5 , 6 , 7 Recently, Berian et al demonstrated that the increase in complications seen in our older patient population was significantly associated with an increased rate of loss of independence and early mortality. 8 Frail surgical patients who suffer loss of independence often are placed in skilled nursing facilities upon discharge from the hospital.…”
Section: Introductionmentioning
confidence: 82%
“…Most studies investigating the relationship between preoperative frailty and postoperative outcome only assess frailty retrospectively [1214], indirectly estimating crucial frailty criteria, such as weakness and exhaustion. Evidence is still lacking as to whether patients benefit from a routine frailty assessment followed by an individualized treatment plan.…”
Section: Introductionmentioning
confidence: 99%
“…Frailty has been shown to be associated with multiple complications after surgery. 6,7 This study investigated the association between frailty and outcomes after elective craniotomy for the resection of brain tumors. 5 Frailty assessment was based on a 5-factor modified frailty index (mFI-5) and classified as nonfrail (mFI-5 = 0), low frailty (mFI = 0.2), or medium to high frailty (mFI > 0.2).…”
Section: Frailty and Outcomes After Brain Tumor Surgerymentioning
confidence: 99%